Perbaikan Pendengaran Pasien Otitis Media Efusi yang Autoinflasi: Laporan Kasus Berbasis Bukti - Firmansyah, Ugiadam Farhan; Suryoadji, Kemal Akbar; Bashirudin, Jenny; Bramantyo, Brastho; Alviandi, Widayat (Cermin Dunia Kedokteran, 2024)
Background: Otitis media with effusion (OME) is the presence of middle ear fluid without acute ear infection signs or symptoms. OME is one of the causes of hearing loss. Chronic asymptomatic OME could be managed by careful waiting for 3 months because it is a self-limiting disease. During surveillance, autoinflation is a beneficial intervention with minimal side effects and high adherence. Objective: To evaluate the effectiveness of autoinflation to improve hearing in otitis media with effusion and hearing loss. Methods: Literature searching was conducted through PubMed, Cochrane, ScienceDirect, Scopus, and EBSCOHost with inclusion and exclusion criteria. The articles were selected and underwent critical appraisal using rapid critical appraisal of systematic review and level of evidence by the Oxford Centre for Evidence-based Medicine in 2011. Result: One systematic review and meta-analysis, or RCT, met the criteria. This article revealed a pooled estimate of RR 1.74; 95% CI [1.22-2.50] with a Z-score of 3.02 (p=0.0025). This result showed substantial significant (p=0.01) heterogeneity (I2=69%). Conclusion: OME patients with hearing loss who performed autoinflation >1 month had a 1.74 times greater chance of achieving hearing improvement than controls. Autoinflation with the Politzer method gives significant results in improving hearing loss. Large-scale RCT research is recommended to evaluate the effectiveness of autoinflation with the Politzer method or other available methods in OME patients with hearing loss.